Uncertainty representation and propagation in structural reliability analysis (Uncertainty in Risk Assessment, 2014)
This chapter considers the problem of uncertainty representation and propagation in the quantification of the reliability of a structure subject to cracking due to fatigue. The application is partly based on Baraldi, Popescu, and Zio. The reliability of a structure is an important issue which needs to be given due attention during all phases of the life cycle of the structure, including design, manufacturing, installation, operation, maintenance, and demolition. For this, mathematical models are developed to describe the evolution of the physical state of the structure. The chapter focuses on pressurized components of nuclear power plant (NPP) systems which are subject to crack propagation initiating from manufacturing flaws under cyclic loading caused by allowed power variations or incidental transients. The chapter presents a case study that considers the problem of assessing the reliability of a structure subject to the propagation of a crack due to fatigue.